Meanings and Symbols of Dalima Relief in Keraton Kasepuhan Cirebon - Husen Hendriyana (Graduate School of Institut Seni Indonesia Yogyakarta, 2014)
Dalima relief is the Keraton Cirebon’s artifacts in periods of Sultan Sepuh I and II (1678-1723). Dalima’s relief is rich of symbolic values with aesthetic expression of its typical culture. There are so many interpretations about Dalima Relief and yet has not been clearly undefined up to these days. This research is using qualitative research with ethnography approach aiming to constructive knowledge and aesthetic interpretation construct. This aesthetic phenomenon has a connection with the events in the past, which will be studied as synchronic or diachronic ways. Diachronic analysis aims to discover a comprehension about culture transformations of Cirebon society from the era of Hindu up to Islamic, while the aesthetic concepts will trace based on value, function and meaning through synchronic analysis with consideration of three culture phenomenon: ideas-activity-artifact, corresponding with the local attributes.Thus ‘Dalima’ is a metaphoric depiction of Q.S Al-Ikhlas (a verse in Holy Qur’an), with etymology of letter compounding ‘dal’ and number five; ‘lima’. These symbols formed by the visual elements of flowers and fruit of Delima (pomegranate), and a pair of white crows. This inspirational object, Dalima is formed as the structure of cosmological acculturative culture (Hindu, Chinese and Islam) with metaphorical representations. Activities and contextual events on this relief made it as Catatan Suluk or lessons to Cirebon’s Mursyid. Norms and theorems which shape as a culture convention on that era, becomes a power of collective traditions which tint the principal and conceptual of Cirebon culture.